Collaborative Justice and Harm Reduction in Cyberspace: Policing Indecent Child Images. (October 2020) - Wilson, Tim J
The exponential increase on the internet of indecent images of children (IIOC) has been followed by a transformation within criminal justice. The scale, nature and rapid technological evolution of such crimes—often of distant initial geographical origin—requires collaborative justice and harm reduction arrangements with internet companies and NGOs. The diminished reach (declining criminal justice interventions) and power (even in identifying crimes for intervention) of state authority with the current collaborative model, however, has resulted in inadequate social regulation and policing in response to IIOC crimes on the surface web. There is a considerable risk that the Online Harms White Paper proposals to establish overarching government authority to generally reduce harmful conduct will not fully resolve problems that go much wider than the technological, commercial and consumer protection on the surface web issues emphasised in that document. Only political choices about funding and fundamental rights compliant legislation can (a) prevent the hollowing out of criminal justice capacity and capabilities to deal with IIOC offenders and (b) ensure an essential compatibility and consistency in police operational ability—including the access sought to anonymised communication data via an encryption key—and legal principles when dealing with IIOC crimes across all levels of the internet, including 'the dark web'. These issues are examined as a case study in civic epistemology about the influence of neoliberalism in technologically focused policy making.